Hakikat Evaluasi Pendidikan Islam Universitas Islam Negeri Sumatera Utara Medan - Filia Bunga Syahbrina; Feri Azlina; Farhan Syarif Muda Harahap (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Evaluation of Islamic education is necessary to assess student progress, the effectiveness of teaching methods, identify student needs, increase student motivation, and raise educational standards. This study employs a qualitative research. Evaluation in Islamic education is also important to raise the standard of instruction by adhering to evaluation principles such as objectivity, overall and sustainable. Benefits of evaluation include more in-depth understanding, character development, arithmetic skill enhancement, arithmetic mean for individuals and groups, and appropriate learning strategies. As long as appropriate evaluation principles are applied, the learning process can be made enjoyable and continuously progress to meet the goals of Islamic education in the best possible way.